Product Development Analysis on Special Snack From Nganjuk “DUMBLEG” as an Effort to Increase The Image Product - Norma Eka Sari Nastiti; Imam Santoso; Nur Hidayat (The Indonesian Green Technology Journal, 2014)
Food and special snack are kind of meal and snack which become the identity of a region. The example of special snack from Nganjuk is Dumbleg. Along with the time, this special snack from Nganjuk is less known by the public and the production gets decreasing in market. This condition is caused by Dumbleg’s quality that is getting down product is not durable and less interesting. Therefore the role of product development is needed. The objective of research was to analyse business place condition of dumleg from Nganjuk, formulates the product development strategy of dumbleg from Nganjuk and formulates the improvement of aesthetics value to increase the image of product to consumer.This research was descriptive which analyzed the problem in the field and then solved it. The sample was obtained by using sampling technique which is Systematic Random Sampling method. The result of research showed that condition of Dumbleg business needs the improvement and development, especially in the process of production. The improvement in the process production of Dumbleg is done by paying attention in the consumer desirability parameter about product quality and aesthetics value. The improvement about product quality is done by applying Hazard Analysis Critical Control Point (HACCP) and hygine sanitation on the right food processing, while the improvement in aesthetics value is implemented by making the perfectness in physical appearance of Dumleg that includes the improvement of size, way of packaging, labeling, and trademarks. Key word: product development, HACCP and hygiene sanitation.